Nevupor an integrated inhaler-nebulizer as a new medical device to regulate asthma of children (5-12 year old) - Niebres, Marcella Caye Justine Julia G.
Children are the most affected age group of the most common chronic disease in the world, which is asthma. One of its consequences is having absences in school, which hinder their early needed growth and development. Aside from school it also affects their play; they can't be physically active because it can trigger an asthma attack. Asthma cannot be cured but only regulated with the help of the inhaler or nebulizer, but children have difficulty or needs assistance in using one when having attacks. Nevupor is a combined reliever and controller medication; a device which uses an atomizer similar to vape but modified to properly breakdown a chemically altered Ventolin Nebule. This device is portable, cheap, rechargeable and easy to use; suitable for children and even for adults. With the help of this device children can regulate an asthma attack independently without supervision, whenever and wherever.